2021
DOI: 10.1016/j.ctrv.2021.102208
|View full text |Cite
|
Sign up to set email alerts
|

European Cancer Organisation Essential Requirements for Quality Cancer Care (ERQCC): Pancreatic Cancer

Abstract: European Cancer Organisation Essential Requirements for Quality Cancer Care (ERQCC) are written by experts representing all disciplines involved in cancer care in Europe. They give patients, health professionals, managers and policymakers a guide to essential care throughout the patient journey.Pancreatic cancer is an increasing cause of cancer mortality and has wide variation in treatment and care in Europe. It is a major healthcare burden and has complex diagnosis and treatment challenges. Care must be carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 148 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…In the present study, patients receiving comfort care showed a significantly lower VAS score and required a lower dose of analgesics than those receiving conventional care, indicating milder pain in patients given comfort care than those receiving conventional care. The reason may be that comfort care effectively relieves the pain of patients through disease education, psychological guidance, and medication instruction and helps patients have a correct understanding of their condition, thereby reducing the use of analgesics [ 18 ]. Moreover, comfort care herein resulted in a better quality of life for patients and lower SAS and SDS scores than conventional care, indicating better quality of life benefits and psychological status management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, patients receiving comfort care showed a significantly lower VAS score and required a lower dose of analgesics than those receiving conventional care, indicating milder pain in patients given comfort care than those receiving conventional care. The reason may be that comfort care effectively relieves the pain of patients through disease education, psychological guidance, and medication instruction and helps patients have a correct understanding of their condition, thereby reducing the use of analgesics [ 18 ]. Moreover, comfort care herein resulted in a better quality of life for patients and lower SAS and SDS scores than conventional care, indicating better quality of life benefits and psychological status management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors and scientific societies such as the ERAS, European Cancer Organization Essential Requirements for Quality Cancer Care, European Society for Clinical Nutrition and Metabolism (ESPEN) ( 2 , 101 – 104 ) have published recommendations and guidelines to define the best management practices for pancreatic cancer patients, including the presence of a nutritionist in the extended multidisciplinary team and pre- and perioperative nutritional care for patients undergoing surgery.…”
Section: Controversial Issues In Clinical Nutrition In Oncologymentioning
confidence: 99%